Fractal Properties Of Earthquakes In Marmara - Ceylan, Savaş (İstanbul Kültür Üniversitesi Yayınları, 2006)
Many geophysical phenomena such as frequency-size distribution of earthquakes, faults, and fractures show multifractal properties. Having fractal distribution requires that number of objects larger than a specified size has power-law dependence. Using power-law relations for statistics of seismicity is not a new subject in geophysics. The Gutenberg and Richter's b-value, which is a good example, defines a relationship between occurrence rates and magnitudes of earthquakes and has been used as the indicator of seismic activity. This study aims to better understand the occurrence systems of earthq uakes around Marmara Sea and the seismic behaviour of the investigation region, by means of multifractals and b-value

Depremlerin büyüklük-frekans dağılımı, faylar ve kırıklar gibi birçok jeofiziksel olgu multifraktal özellikler gösterirler. Fraktal dağılım, belirli bir büyüklükten daha büyük nesnelerin sayısının, büyüklükleri ile üstel ilişki göstermesini gerektirir. Deprem etkinliğinin istatistiksel olarak incelenmesinde üstel ilişkilerin kullanılması, jeofizikte yeni bir konu değildir. Deprem oluşum sayıları ve büyüklükleri arasındaki ilişkiyi tanımlayan Gutenberg ve Richter'in b-değeri buna güzel bir örnektir ve sismik etkinliğin göstergesi olarak kabul edilir. Çalışma, Marmara Denizi civarında oluşmuş depremlerin oluşum sistemlerinin ve inceleme alanının sismik davranışının, multifraktal yapılar ve b-değeri yardımıyla daha iyi anlaşılmasını amaçlamaktadır.
Keywords: Earthquake; multifractal analysis; fractal dimensions; b-value; Marmara; Deprem; multifractal analizi; fraktal boyutları; b değeri